2006
DOI: 10.1002/hep.21017
|View full text |Cite
|
Sign up to set email alerts
|

CD4+ T cells contribute to postischemic liver injury in mice by interacting with sinusoidal endothelium and platelets

Abstract: The mechanisms by which T cells contribute to the hepatic inflammation during antigenindependent ischemia/reperfusion (I/R) are not fully understood. We analyzed the recruitment of T cells in the postischemic hepatic microcirculation in vivo and tested the hypothesis that T cells interact with platelets and activate sinusoidal endothelial cells, resulting in microvascular dysfunction followed by tissue injury. Using intravital videofluorescence microscopy, we show in mice that warm hepatic I/R ( L iver injury … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
97
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(104 citation statements)
references
References 51 publications
5
97
0
2
Order By: Relevance
“…The development of in vivo imaging techniques, such as intravital microscopy (IVM) further allows to track cells in live animals over longer time periods in organs including cremaster muscle, liver, lung, brain and kidney (Figure 1C) (56,57), and have been greatly beneficial in analysing dynamic interaction between platelets and leukocytes (e.g. duration of interactions and behavioural changes in leukocytes and/or platelets upon contact) (10,53,55,58–61). …”
Section: Methods To Measure Plasmentioning
confidence: 99%
See 3 more Smart Citations
“…The development of in vivo imaging techniques, such as intravital microscopy (IVM) further allows to track cells in live animals over longer time periods in organs including cremaster muscle, liver, lung, brain and kidney (Figure 1C) (56,57), and have been greatly beneficial in analysing dynamic interaction between platelets and leukocytes (e.g. duration of interactions and behavioural changes in leukocytes and/or platelets upon contact) (10,53,55,58–61). …”
Section: Methods To Measure Plasmentioning
confidence: 99%
“…Early epifluorescence IVM studies primarily utilised intravascular administration of nonspecific cell dyes (e.g. rhodamine 6G), or ex vivo labelling and adoptive transfer of platelets into donor animals (58,62–64). However, the lack of clear distinctions between specific cell types using unspecific dyes limits the analysis of PLAs.…”
Section: Methods To Measure Plasmentioning
confidence: 99%
See 2 more Smart Citations
“…Several reports have shown that CD4 Ï© , but not CD8 Ï© , T cells are recruited into the postischemic liver within 1 h of reperfusion and regulate hepatic inflammation (20,44). These studies demonstrated that depletion or deficiency of CD4 Ï© T cells attenuates liver injury, hepatic neutrophil infiltration, and platelet-endothelial cell interaction.…”
mentioning
confidence: 92%